P4-S3.05 Clinical titres and stability of Trichomonas vaginalis RNA in urine specimens. (10th July 2011) - Catania, M; Bennett, C; Pae, A; Weinbaum, B; Getman, D
Abstract : Background: This study estimated the range of concentrations of Trichomonas vaginalis (TV) present in naturally infected female urine specimens and evaluated the ability of the APTIMA Trichomonas vaginalis (ATV, Gen-Probe Incorporated) Assay to detect a clinically-relevant amount of TV cells spiked into TV-negative male and female urine samples and stored at various temperatures. Methods: Female urine samples collected as part of a prospective, multicenter US clinical trial were tested with the ATV Assay, a nucleic acid amplification test for the diagnosis of TV infection in asymptomatic and symptomatic women. To determine TV cell titres, serial dilutions of TV-positive urine samples were tested and results were compared to results from serial dilutions of a laboratory culture of TV with a known cell titre. To assess the stability of TV cells in urine samples, 10 male and 10 female urine samples from non-infected volunteer donors were spiked with a cultured strain of TV, stored at 4°C, 20°C and 30°C, and tested daily for up to 14 days with the ATV assay. Results: Of 39 randomly selected TV-positive female urine samples, the median titre in unprocessed samples was 311 cells/ml (mean=2040 cells/ml; SD=4765 cells/ml), with a range of 2–28 430 cells/ml. Of these 39, 87.2% (34/39) had a TV cell titre of ≥20 cells/ml in neat urine see Abstract P4-S3.05 figure 1 . To assess stability of TV cells in urine, freshly collected male and female urine samples from volunteer donors were spiked with TV to 20 cells/ml (4 cells/reaction in the ATV assay), stored at various temperatures, and then tested with the ATV assay. For samples stored at 4°C, the ATV assay was 100% reactive for both male and female samples after 14 days of storage. For samples stored at 20°C, male samples were 100% reactive after 7 days storage, while female samples were 100% reactive after 6 days of storage. For samples stored at 30°C, 100% reactivity was obtained at 2 days storage for male samples and 4 days storage for female samples. Conclusions: This study shows urine samples from women infected with TV have a wide range of cell titres, with an average of ∼2000 TV cells/ml. TV can be detected for 14 days when stored refrigerated or for about 1 week at 20°C. The use of sensitive, automated molecular tests such as the ATV assay for testing urine samples should facilitate screening for TV.